Rapid Alleviation of Parkinson’s Disease Symptoms via Electrostimulation of Intrinsic Auricular Muscle Zones - Cakmak, Yusuf O.; Apaydin, Hülya; Kiziltan, Güneş; Gündüz, Ayşegül; Ozsoy, Burak; Olcer, Selim; Urey, Hakan; Cakmak, Ozgur O.; Ozdemir, Yasemin G.; Ertan, Sibel (Frontiers in Human Neuroscience, 2017)
Background Deep brain stimulation of the subthalamic nucleus (STN-DBS) and the pedunculopontine nucleus (PPN) significantly improve cardinal motor symptoms and postural instability and gait difficulty (PIGD), respectively, in Parkinson’s disease (PD). Objective and Hypothesis Intrinsic auricular muscle zones (IAMZs) allow the potential to simultaneously stimulate the C2 spinal nerve, the trigeminal nerve, the facial nerve, and sympathetic and parasympathetic nerves in addition to providing muscle feedback and control areas including the STN, the PPN and mesencephalic locomotor regions. Our aim was to observe the clinical responses to IAMZ stimulation in PD patients. Method Unilateral stimulation of an IAMZ, which includes muscle fibers for proprioception, the facial nerve, and C2, trigeminal and autonomic nerve fibers, at 130 Hz was performed in a placebo- and sham-controlled, double-blinded, within design, two-armed study of 24 PD patients. Results The results of the first arm (10 patients) of the present study demonstrated a substantial improvement in Unified Parkinson’s Disease Ratings Scale (UPDRS) motor scores due to 10 minutes of IAMZ electrostimulation (p=0.0003, power: 0.99) compared to the placebo control (p=0.130). A moderate to large clinical difference in the improvement in UPDRS motor scores was observed in the IAMZ electrostimulation group. The results of the second arm (14 patients) demonstrated significant improvements with dry needling (p=0.011) and electrostimulation of the IAMZ (p=0.001) but not with sham electrostimulation (p=0.748). In addition, there was a significantly greater improvement in UPDRS motor scores in the IAMZ electrostimulation group compared to the IAMZ dry needling group (p<0.001) and the sham electrostimulation (p<0.001) groups. The improvement in UPDRS motor scores of the IAMZ electrostimulation group (ΔUPDRS=5.29) reached moderate to high clinical significance, which was not the case for the dry needling group (ΔUPDRS=1.54). In addition, both arms of the study demonstrated bilateral improvements in motor symptoms in response to unilateral IAMZ electrostimulation. Conclusion The present study is the first demonstration of a potential role of IAMZ electrical stimulation in improving the clinical motor symptoms of PD patients in the short term.